O ENSINO-APRENDIZAGEM DE ESTUDANTES COM DUPLA EXCEPCIONALIDADE (TEA NÍVEL 1 /AHSD): uma intervenção pedagógica no Núcleo de Atividades de Altas Habilidades/Superdotação - NAAHS/MA. - CIPRIANO, Jailson Araujo (2021)
This dissertation aimed to develop a Notebook for Pedagogical Interventions in Socioemotional and Cognitive Skills, through educational interventions with the collaboration of NAAHS teachers, to assist in the teaching-learning process of students with dual exceptionality (TEA LEVEL 1 /AHSD). To that effect, this research is characterized as a pedagogical intervention. The research site was the Center for Activities for High Abilities/Giftness – Joãosinho Trinta – NAAHS. For our data collection we used instruments, observations, semi-structured interviews, semi structured questionnaires, focus groups and document analysis. Our research sample involved 03 (three) teachers, 01 (one) Pedagogical Coordinator and 01 (one) student with dual exceptionality (ASD level 1/High abilities and giftedness) enrolled in Basic Education, and who was necessarily attending the NAAHS. Qualitative data analysis was performed using Bardin's Content Analysis technique, and quantitative analysis was performed using graphs and frequency calculation, prepared using the Excel program. Interventions were collaboratively conducted in order to develop socio emotional and cognitive skills through applied research, which resulted in the Booklet for Pedagogical Interventions in Socio-emotional and Cognitive Skills. The research revealed that some socio-emotional skills are worked on by NAAHS teachers, and from the findings, it was obtained: 100% of teachers responded that they develop interventions to improve autonomy and self-confidence; 66.66% develop interventions to develop emotional stability and self-development. As for the student's needs concerning the psychosocial aspects demonstrated by the student, 100% of the teachers said that they have difficulty in social interaction; 100% said they have difficulty in making new friends; 66% expressed that they have a slight attachment to routines; 66.66% indicated that they have anxiety; 66.66% stated that the student has difficulty in showing affection; 66.66% stated that they have difficulty maintaining eye contact; and 66.66% stated that they have difficulty concentrating. From this investigation, it was found that the student with dual exceptionality needs interventions mainly to: strengthen conative and executive functions, anxiety, and self-esteem; to improve social interaction; to better understand and improve emotions; maintain eye contact; and to better understand figurative and non-verbal language. Our main results point to the need for adequate training and in-service training and for public policies that will be materialized in continuing education programs. Our study also revealed the absence of specific instruments to identify double exceptionality with Autistic Spectrum Disorder level 1 and high abilities/giftedness, confirming that these students need a correct diagnosis in order to implement specific interventions.